Key determinants of brand perception among clothing consumers in Machala, Ecuador (Journal SCIENCEVOLUTION, 2025)
The primary objective of this article was to analyze the factors influencing brand perception among clothing consumers in the city of Machala. A quantitative methodology was employed, characterized by a correlational design and descriptive scope. The study utilized a survey as the primary research technique, with a questionnaire comprising 27 items aligned with the study variables serving as the data collection instrument. Responses were assessed using a 5-point Likert scale. For sample selection, a non-probabilistic convenience sampling method was applied, selecting 380 young individuals aged 18 to 30 years. Data processing was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) statistical technique to derive correlational insights among the study variables. The results demonstrated that key factors such as product quality, brand awareness, brand image, and consumer trust are closely associated with consumers' brand perception. Consequently, it was concluded that comprehensive marketing strategies must be implemented to prioritize these aspects, thereby optimizing the relationship between brands and consumers.
Keywords: Brand perception; Quality; Awareness; Image; Trust